Genomic insights into ESBL-producing Escherichia coli isolated from non-human primates in the Peruvian Amazon - Bazalar-Gonzales, Jhonathan; Silvestre-Espejo, Thalía; Rodríguez Cueva, Carmen; Carhuaricra Huamán, Dennis; Ignación León, Yennifer; Luna Espinoza, Luis; Rosadio Alcántara, Raúl; Maturrano Hernández, Lenin (Frontiers in Veterinary Science, 2024)
Introduction: Extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae are on the WHO priority pathogens list because they are associated with high mortality, health-care burden, and antimicrobial resistance (AMR), a serious problem that threatens global public health and should be addressed through the One Health approach. Non-human primates (NHP) have a high risk of acquiring these antibiotic-resistant bacteria due to their close phylogenetic relationship with humans and increased anthropogenic activities in their natural environments. This study aimed to detect and analyze the genomes of ESBL-producing Escherichia coli (ESBL-producing E. coli) in NHP from the Peruvian Amazon. Materials and Methods: We collected a total of 119 fecal samples from semi-captive Saguinus labiatus, Saguinus mystax and Saimiri boliviensis, and captive Ateles chamek, Cebus unicolor, Lagothrix lagothricha and Sapajus apella in the Loreto and Ucayali regions, respectively. Subsequently, we isolated and identified E. coli strains by microbiological methods, detected ESBL-producing E. coli through antimicrobial susceptibility tests following CLSI guidelines, and analyzed their genomes using previously described genomic methods. Results: We detected that 7.07% (7/99) of E. coli strains: 5.45% (3/55) from Loreto and 9.09% (4/44) from Ucayali, expressed ESBL phenotype. Genomic analysis revealed the presence of high-risk pandemic clones, such as ST10 and ST117, carrying a broad resistome to relevant antibiotics, including three blaCTX-M variants: blaCTX-M-15, blaCTX-M-55 and blaCTX-M-65. Phylogenomic analysis confirmed the clonal relatedness of high-risk lineages circulating at the human-NHP interface. Additionally, two ESBL-producing E. coli strains were identified as EPEC (eae) and ExPEC according to their virulence profiles, and one more presented a hypermucoviscous phenotype. Discussion: We report the detection and genomic analysis of seven ESBL-producing E. coli strains carrying broad resistome and virulence factors in NHP from two regions of the Peruvian Amazon. Some of these strains are closely related to high-risk pandemic lineages previously reported in humans and domestic animals, highlighting the negative impact of anthropogenic activities on Amazonian wildlife. To our knowledge, this is the first documentation of ESBL-producing E. coli in NHP from the Amazon, underscoring the importance of adopting the One Health approach to AMR surveillance and minimizing the potential transmission risk of antibiotic-resistant bacteria at the human-NHP interface.